Pengaruh Brand Alat Seduh terhadap Persepsi Citarasa Kopi pada Tefa Javanica Politeknik Negeri Banyuwangi - Nugroho Dwi Prasojo; Jamilah Jamilah; Deka Rachmana Putra; Mohamad Ilham Hilal (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study investigates the influence of coffee brewing device branding on the sensory perception of coffee flavor at TEFA Javanica, Politeknik Negeri Banyuwangi. Focusing on three V60 dripper brands—Hario (Japanese brand), Indotara (local generic brand), and One Two Cup (local brand with English naming)—the research employs an experimental quantitative approach combining blind and branded taste tests. The blind test eliminates brand influence, allowing assessment of the inherent coffee taste, while the branded test examines how brand expectations affect flavor experience and consumer perception. Sensory evaluation follows the Specialty Coffee Association's standardized cupping protocol, assessing aroma, taste, aftertaste, balance, and overall impression. Data from 45 purposively selected experienced coffee tasters were analyzed using the McNemar test to statistically compare preferences between blind and branded conditions. Results show significant brand effects on consumer perception for two of the three brands tested, highlighting branding’s role in shaping sensory experience. These findings offer valuable insights for coffee producers and marketers to optimize brewing device selection and branding strategies, enhancing customer satisfaction and competitive positioning. Academically, the study enriches literature on sensory branding in coffee, emphasizing the importance of equipment branding in specialty coffee markets. This research also lays groundwork for future studies exploring marketing and consumer psychology aspects within the specialty coffee industry.